2014
DOI: 10.1007/s00344-014-9467-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Brassinosteroid and Brassinosteroid Mimic on Improving Photosynthesis, Lipid Peroxidation, and Rice Seed Set under Heat Stress

Abstract: The application of brassinosteroids (BRs) has been reported to alleviate heat stress. This study investigated the effect of 7,8-dihydro-8a-20-hydroxyecdysone (DHECD)-a BR mimic-by comparison with 24-epibrassinolide (EBR) on the changes in photosynthetic performance, lipid peroxidation, and rice seed set. The results demonstrated that 10 28 M EBR and 10 27 M DHECD had the best actions to counteract the lethal heat temperature of 47°C for 2 h indicated by a reduction in the number of wilted leaves and an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 57 publications
2
30
0
Order By: Relevance
“…Pretreatment with 24-epibrassinolide (1 mg dm -3 ) reduced MDA accumulation by 35 %. A similar effect was observed in rice plants grown at high d/n temperatures of 40/30 °C for 7 d (Thussagunpanit et al 2015b). In eggplants at d/n temperatures of 43/38 °C (8 d), 0.1 μM 24-epibrassinolide reduced the MDA content by 16 % compared to plants that were not treated (Wu et al 2014b).…”
Section: The Structure and Properties Of Cell Membranessupporting
confidence: 70%
“…Pretreatment with 24-epibrassinolide (1 mg dm -3 ) reduced MDA accumulation by 35 %. A similar effect was observed in rice plants grown at high d/n temperatures of 40/30 °C for 7 d (Thussagunpanit et al 2015b). In eggplants at d/n temperatures of 43/38 °C (8 d), 0.1 μM 24-epibrassinolide reduced the MDA content by 16 % compared to plants that were not treated (Wu et al 2014b).…”
Section: The Structure and Properties Of Cell Membranessupporting
confidence: 70%
“…Plants treated with EBR exhibited increases in ETR and q P , which are related to higher energy absorption of photons and subsequent increased flow of energy for the excitation of electrons accepted by plastoquinone (Buonasera et al 2011). Thussagunpanit et al (2015a) studied the action mechanisms of EBR in Oryza sativa plants and reported increases in U PSII after EBR application. Research conducted by Li et al (2015) showed that EBR increases the proportion of open PSII reaction centres, improving the efficiency of the capture of light energy for the electron transport chain.…”
Section: Discussionmentioning
confidence: 99%
“…In grape seedlings (V. vinifera L.) with 10% PEG stress, the application of 0.105-0.42 µM 24-epiBL significantly increased the chlorophyll content (Chl a, Chl b, and Chl), maximal fluorescence, F v /F m , and NPQ, to improve drought tolerance [38]. Thussagunpanit and co-workers sprayed the foliage of rice (Oryza sativa L.) with 0.1 µM 24-epiBL and reported that 24-epiBL improved P n , G s , F v /F m , and Chl a, Chl b, and Chl contents with a reduction in C i to protect the plants from heat stress (47 • C) [39].…”
Section: Photosynthesismentioning
confidence: 99%